Knife crime in England and Wales (Ius Novum, 2021)
The article is an attempt to synthesise knife crime in England and Wales. The article aims not only to present the phenomenon through the prism of the regulations in force, the prevention system and the research explaining its occurrence but also to encourage readers to have a close look at the phenomenon in Poland. The research conducted made it possible to determine that scarce data concerning Polish reality justify the need to deepen this knowledge by examining the ways in which the problem is dealt with in the Anglo-Saxon environment and possibly by extending domestic statistics.
Keywords: knife crime; Anglo-Saxon solutions; law in England and Wales; prevention programme; Stop-and-Search